1996
DOI: 10.1097/00001888-199608000-00017
|View full text |Cite
|
Sign up to set email alerts
|

An innovative CME program in cardiology for primary care practitioners

Abstract: The authors describe an innovative continuing medical education (CME) program they developed to improve the ability of community practitioners to manage common cardiology problems. The program includes an objective structured clinical examination (OSCE) with nine standardized patient (SP) stations. The SPs are trained to use checklists to assess the examinees' clinical skills, and to enter the checklist data directly into computers located within each of the examining rooms. Checklists cover the participants' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Although objective structured clinical examinations and standardized patients have been used in various educational settings, their use in CME programming has been reported infrequently, and usually in relation to needs assessments or construction of improved educational tools for other physicians. [21][22][23][24] This issue has recently been reviewed. 25 Nonetheless, this evaluation format has been shown to be both valid and reliable when the content of the objective structured clinical examination directly relates to the objectives of the educational intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although objective structured clinical examinations and standardized patients have been used in various educational settings, their use in CME programming has been reported infrequently, and usually in relation to needs assessments or construction of improved educational tools for other physicians. [21][22][23][24] This issue has recently been reviewed. 25 Nonetheless, this evaluation format has been shown to be both valid and reliable when the content of the objective structured clinical examination directly relates to the objectives of the educational intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, other CME programs have found that community physicians are reluctant to be involved if the evaluation is perceived not to be confidential. 21 By incorporating the standardized patient component into the objective structured clinical examination evaluation, both physician competence and performance could be assessed. In the pretest, group and individual deficits could be identified against an objectively defined 168 clinical competence check list, which validated our previous needs assessment.…”
Section: Discussionmentioning
confidence: 99%
“…17 The Internet offers a potential opportunity to provide medical education where, when, and at the pace needed by the physician. [7][8][9][10][11][12][13] However, the Internet is unregulated and uncontrolled. It is a new paradigm for providing education, one that some universities and medical schools, the traditional sources of CME, may be ill-equipped to use.…”
Section: Discussionmentioning
confidence: 99%
“…Course participants were invited to repeat the self-assessment program 3 months later as an evaluation strategy. O'Brien et al 22 report using a nine-station OSCE to identify the educational needs of family physicians. Participants received the results immediately and discussed their performance and learning needs with a cardiologist.…”
Section: Parboosinghmentioning
confidence: 99%